Organic Syntheses 2005
DOI: 10.1002/0471264229.os081.03
|View full text |Cite
|
Sign up to set email alerts
|

dl ‐Selective Pinacol‐Type Coupling Using Zinc, Chlorosilane, and Catalytic Amounts of Cp 2 VCl 2 ; dl ‐1,2‐dicyclohexylethanediol

Abstract: Dichlorodicyclopentadienylvanadium Chlorotrimethylsilane Cyclohexanecarboxaldehyde 1,2‐Cyclohexylethanediol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…These reactions give two types of the complexes. The reaction with titanocene dichloride (1) forms Cp 2 Ti(dcmb) 2 (3) that have both dcmb ligands bonded through the oxygen atoms. Bonding of the dcmb ligands .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These reactions give two types of the complexes. The reaction with titanocene dichloride (1) forms Cp 2 Ti(dcmb) 2 (3) that have both dcmb ligands bonded through the oxygen atoms. Bonding of the dcmb ligands .…”
Section: Discussionmentioning
confidence: 99%
“…Its recrystallization from wet MeCN gives dcmbHÁH 2 O that was used for the reactions with bent metallocenes. The X-ray diffraction analysis of dcmbHÁH 2 O has shown that the dcmb is protonated at oxygen atom (see Fig. 1).…”
Section: Syntheses and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations